Analisis penulisan assessment dan plan CPPT apoteker pada pasien community acquired pneumonia (CAP) Rawat inap di rumah sakit X Padang - Amelia, Ayu; Nasif, Hansen; Sari, Yelly Oktavia (Journal of Pharmaceutical and Sciences, 2023)
The Integrated Patient Development Record (CPPT) is a standardized form of documentation used by healthcare professionals to record the development of a patient's condition. It follows the SOAP (Subjective, Objective, Assessment, Plan) method. Inaccurate or incomplete CPPT data can negatively impact the quality of care provided to patients, affecting the effectiveness of their treatment. This study aims to analyze the accuracy of the Assessment and Plan written by pharmacists for inpatient community pneumonia patients in the pulmonary and internal medicine department of X Padang Hospital. The inclusion criteria in this study were medical records of community pneumonia patients with CPPT written by pharmacists. Medical records that met the criteria for inclusion as research subjects were 38 cases. From this study, the results of the analysis of the accuracy of writing the assessment and plan pharmacists were obtained, and none (0%) of the 38 CPPTs analyzed were written correctly.